Problems of Development of Bioethics in Therepublic of Azerbaijan - Javadly, Gamar (Scholarya Demo Journal of Ruby, 2019)
Bioethics is a scientific field that predetermines the new philosophicalthought of modernity. The formation and development of this scientificdiscipline is closely connected with the transformation of traditional ethics ingeneral and medical ethics separately. The interest in bioethics is primarily dueto the special attention of the public to human rights, the testing of newtechnologies and medical devices over people, which, in turn, have created alot of problems that require solving legal and spiritual regulation.Today, modern bioethics covers a wide range of scientific and practicalareas of activity. First of all, bioethics is an interdisciplinary subject that studiesthe causes and consequences of scientific and technical development ofbiomedicine. Doctors, biologists, philosophers, theologians, lawyers,psychologists, political scientists and other specialists from various fields areinvolved in solving bioethical problems. Secondly, bioethics is a system ofacademic research and education. In many countries of the world, bioethics asan academic subject is studied in children’s institutions, schools and lyceums,in medical, biological, philosophical, legal, theological, and other departmentsof universities. Thirdly, the bioethics institute with a widely developed systemof public organizations. Such organizations as UN, UNESCO, ISESCO, theEuropean Union, the World Health Organization, many international,governmental and public structures, regional and local ethical committees dealwith problems of bioethics.In Azerbaijan, after the renewal of state sovereignty, since the 90s of thelast century, attitudes towards the bioethical problems of society are beingformed. The development of bioethics in Azerbaijan is largely due to thesupport of UNESCO. Compared to other developed countries, Azerbaijan lagsa little behind in drafting ethical and legal standards, conducting scientificinnovations and research on bioethics. In particular, such an important area asthe rights of the patient, informed coordination, the investigation of deaths, theethical and legal aspects of the pharmaceutical business of doctors have not been studied enough. And it is forgotten to add to the socio-political andscientific trends of bioethics of the religious aspect, which is very important insolving complex ethical and moral-spiritual national values.